Otimização do tratamento do bagaço de caju com divinilsulfona visando sua utilização como suporte para imobilização da lipase do tipo A de Candida Antarctica - Lima, Paula Jéssyca Morais (2020)
An agro-industrial residue, cashew apple bagasse, was used as a support for immobilizing lipase A from Candida antarctica (CALA). CALA is a very attractive biocatalyst, has high thermostability, selectivity for trans fatty acids, stability in acid pH and high chemoselectivity in relation to amine groups. Cashew apple bagasse, in addition to having a very low cost and reducing environmental impacts, as it is a biodegradable material, also has good physical and mechanical properties favorable to enzymatic immobilization. Among immobilization methods, adsorption, a simple and widely used method, allows the interaction between the support and the enzyme, resulting in better enzymatic stabilization. In this study, divinyl sulfone (DVS) was used to modify the support structure and, thus, test its effect on enzyme-support interactions. To optimize the treatment of cashew apple bagasse with DVS for immobilization of CALA, an advanced experimental design by the Taguchi method was used, with a standard orthographic L16 matrix (the 'L' and the '16' represent the Latin square and the number of experiments, respectively), where five factors at four levels were analyzed (DVS concentration: 1, 3, 5 and 7.5; buffer molarity: 5, 25, 100 and 350 mM; pH: 3, 5, 7 and 12,5; temperature: 4, 15, 25 and 30 °C and optimization time: 0.5, 3, 12 and 24 h), in order to maximize the activity of the biocatalyst. For the immobilization process, 1.0 mg of enzyme per g of support was used in the presence of 0.01% Triton-X and 5 mM sodium phosphate buffer and pH 7.0, for 24 h and 25 °C, under controled stirring. After immobilization, the biocatalysts were incubated in 100 mM bicarbonate buffer at pH 10.0 (1:10 w/v) at 25 °C for 24 h, and then in 1 M EDA at pH 10.0 also for 24 ha 4 °C. After the experimental planning was concluded, the ideal conditions for preparing the support were: DVS concentration: 4.5 M, buffer molarity: 5 mM, pH: 3; temperature: 30 °C and activation time: 12 h, obtaining a derivative activity of 6.8 U/g and immobilization yield of 24%. The value of the derivative activity provided by the software was 6.5 U/g. FTIR and Elemental Analysis confirmed the immobilization of CALA in BAG-DVS, at 1712 cm-1 and with an increase of 3.71% nitrogen, respectively. The TGA analysis showed degradation of the BAG, BAG-DVS and BAG-DVS-CAL samples at 500 ºC with weight loss, respectively, of 51.9%, 49.9% and 55.7%. The immobilization of CALA in cashew apple bagasse promoted an increase in thermal stability at 70 °C and pH 5, 7 and 9. In addition, after eight months of storage, the activity of the biocatalyst decreased only 50%. The results showed that the pretreated BAG is promising for immobilizing enzymes, improving the stability of CALA.